2016
DOI: 10.1177/0886260515588535
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors That Contribute to Positive Change in a Diverse, Group-Based Male Batterer Intervention Program

Abstract: Although batterer intervention programs (BIPs) are often mandated for perpetrators of intimate partner violence, the precursors and mechanisms of change operating within these programs remain unclear. The purpose of this qualitative study was to examine the perceptions and experiences of participants in a diverse, group-based male BIP to better understand factors facilitating positive change. Data were gathered through individual interviews with 15 men and were analyzed using grounded theory. Findings suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 25 publications
4
50
1
1
Order By: Relevance
“…Qualitative studies are well suited to address "when and how" BIPs work; such studies can provide detailed descriptions of processes as they occur and thus can help identify what aspects of BIPs might motivate and encourage perpetrators toward behavioral change. A growing body of qualitative research on BIPs from the United States and elsewhere has begun to emerge (Boira, del Castillo, Carbajosa, & Marcuello, 2013;Buchbinder & Eisikovits, 2008;Chovanec, 2009Chovanec, , 2012Gray, Lewis, Mokany, & O'Neill, 2014;Holtrop et al, 2017;Morrison et al, 2016;Morrison et al, 2017;Pandya, 2009;Pandya & Gingerich, 2002;Parra-Cardona et al, 2013;Rosenberg, 2003;Scott & Wolfe, 2000;Shamai & Buchbinder, 2010;Silvergleid & Mankowski, 2006). Some have explored the perspectives of professionals involved in BIPs on what factors contribute to change among perpetrators and/or the strategies involved in engaging clients in the process (Chovanec, 2009(Chovanec, , 2012Morrison et al, 2017;Shamai & Buchbinder, 2010;Silvergleid & Mankowski, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies are well suited to address "when and how" BIPs work; such studies can provide detailed descriptions of processes as they occur and thus can help identify what aspects of BIPs might motivate and encourage perpetrators toward behavioral change. A growing body of qualitative research on BIPs from the United States and elsewhere has begun to emerge (Boira, del Castillo, Carbajosa, & Marcuello, 2013;Buchbinder & Eisikovits, 2008;Chovanec, 2009Chovanec, , 2012Gray, Lewis, Mokany, & O'Neill, 2014;Holtrop et al, 2017;Morrison et al, 2016;Morrison et al, 2017;Pandya, 2009;Pandya & Gingerich, 2002;Parra-Cardona et al, 2013;Rosenberg, 2003;Scott & Wolfe, 2000;Shamai & Buchbinder, 2010;Silvergleid & Mankowski, 2006). Some have explored the perspectives of professionals involved in BIPs on what factors contribute to change among perpetrators and/or the strategies involved in engaging clients in the process (Chovanec, 2009(Chovanec, , 2012Morrison et al, 2017;Shamai & Buchbinder, 2010;Silvergleid & Mankowski, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified the therapists as key in producing an internal change process (Boira et al, 2013;Holdsworth et al, 2019;Holtrop et al, 2017;Parra-Cardona et al, 2013;Shamai & Buchbinder, 2010). In Shamai andBuchbinder (2010, p. 1344) participants likened their facilitator to a 'teacher and father'.…”
Section: Reasons Given For Programme Completion and Non-completionmentioning
confidence: 99%
“…Battered women's advocates, activists, and practitioners 2 struggled with arrested women being sent to these programs, as the dominant intervention model for addressing IPV was Batterer Intervention Programming (BIP). After all, BIPs, such as Alternatives to Domestic Aggression (Holtrop et al, 2017), the Duluth Domestic Abuse Intervention Project (DAIP; Pence & Paymar, 1993), and Emerge (Edelson & Tolman, 1992), were developed in the 1970s and 1980s to address heterosexual male violence used against their intimate female partners. BIP interventions were specifically designed to address the sociocultural underpinnings and institutionalized infrastructure of the coercive control that abusive men leverage against their female partners (Stark, 2007).…”
Section: Programming For Women Who Use Forcementioning
confidence: 99%